A Milestone: Approval of CEUS for Diagnostic Liver Imaging in Adults and Children in the USA - Seitz, K.; Strobel, D. (Ultraschall in der Medizin - European Journal of Ultrasound, 2016)
The approval of microbubbles with the inert gas sulfur hexafluoride (SF6) and a palmitic acid shell (SonoVue®, Bracco Geneva, CH) for the diagnostic imaging of liver tumors in adults and children by the FDA in the United States represents a milestone for contrast-enhanced ultrasound (CEUS).This warrants a look back at the history of the development of CEUS. The first publications based on echocardiographic observations of right ventricular contrast phenomena caused by tiny air bubbles following i. v. injection of indocyanine green appeared around 1970 123. A longer period of sporadic publications but no real progress then followed since, in contrast to X-ray methods, ultrasound works quite well without a contrast agent.It is noteworthy that the foundations for further development were primarily laid in Europe. The development and approval (1991) of the contrast agent Echovist® by a German contrast manufacturer for echocardiography unsuitable for passing through lungcapillaries 45 resulted in the first extracardiac indications, e. g. for detecting retrovesical reflux and tubal patency, in the mid-1980 s 678. The sensitivity of color Doppler was not able to compensate for the lack of an ultrasound contrast agent compared to CT with its obligatory contrast administration.Studies of SHU 508 – microbubbles of air moderately stabilized with galactose and palmitic acid – began in 1990 9101112131415 and the contrast agent was then introduced in 1995 in Germany as Levovist®. The most important publications by Blomley, Cosgrove, Leen, and Albrecht are named here on a representative basis 1617181920.SHU 508 along with other US contrast agents provided impressive proof of the superiority of CEUS for the diagnosis of liver metastases. However, practical application remained complicated and required skill and technical know-how because of a lack of suitable software on US units 2122232425. The monograph regarding the use of contrast agent in the liver by Wermke and Gaßmann is impressive but unfortunately only available in German 26. In addition to being applied in the heart and the liver, CEUS was first used in transcranial applications 27 and in vessels 28, the kidneys 29, and the breast 30. Measurements at transit times were also of particular interest 31. It was difficult to convince ultrasound device manufacturers of the need to adapt US units to US contrast agents and not vice versa.The breakthrough came with low MI phase contrast inversion and the introduction of SonoVue® in many European countries in 2001. This more stable US contrast agent is easy to use and is becoming indispensable in diagnostic imaging of the liver 323334353637383940. Studies have shown its excellent tolerability 41 and diagnostic reliability comparable to that of MDCT and MRI in the liver 4243. Today it would be unimaginable to diagnose liver tumors without CEUS 44. This also applies to very small lesions 4546.EFSUMB published the first CEUS guidelines in 2004 47 which have since been reissued and divided into hepatic 48 and extrahepatic applications 49. The first recommendations regarding quantitative assessment have also been published 50.The increasing scientific interest in CEUS is evident based on the greater number of PubMed hits for Echovist® (ca. 130), Levovist® (ca. 500) and SonoVue® (ca. 1500) as well as on the fact that publications regarding CEUS comprise almost 20 % of UiM/EJU articles in the last 10 years. The number of CEUS articles in UiM/EJU continues to be high 51525354555657585960616263646566676869707172737475.In the clinical reality, CEUS has been able to become established alongside CT and MRI according to the saying “better is the enemy of good” 76 as the method of choice after B-mode ultrasound in the evaluation of liver tumor malignancy in Germany, where the technically challenging method is promoted. In the case of unclear CT and MRI findings, CEUS performed by an experienced examiner/clinician often provides the solution, particularly in the case of small lesions, and is the last resort before US-guided biopsy 4546. However, there is a lack of competent CEUS examiners and Germany continues to be the world champion of X-ray examinations with no noticeable reverse trend. In almost every doctor’s office and hospital, ultrasound costs are by far not fully covered, resulting in an extremely high frequency of CT use with CT being available to everyone regardless of insurance status.The USA is now in the starting position for CEUS. It will be exciting to see how the method will develop there. The FDA’s decision to approve sulfur hexafluoride (Lumason® = SonoVue®) should be considered against the background of the radiation exposure caused by CT examinations and the fact that MRI using gadolinium-containing contrast agents is no longer considered noninvasive because of nephrogenic systemic fibrosis (NSF) and the accumulation of the agent in the cerebrum. An essential point of the campaign regarding the avoidance of diagnostic radiation exposure triggered in the USA by the publications of Brenner et al. 7778 was that the agent was approved for use in the liver even for children 7980 – still off label in Europe – without additional comprehensive studies due to the available scientific results and the very low side effects profile of Lumason® (= SonoVue®). It is admittedly unclear why other indications (except the heart which has been approved since 2014) are excluded even though the microbubbles as a pure blood pool contrast agent can be diagnostically used in the entire vascular system and bed of all organs. To our knowledge, there is no such restriction on the approval of X-ray contrast agents.Like echocardiography and emergency ultrasound, CEUS began in Europe but will probably only establish its final diagnostic value as a “reimport”.This is a major opportunity to permanently define the role of Ultrasound as a highly valuable, patient-centered imaging method in the German health care system.This may prompt some of our international readers to reflect upon the role of CEUS in their own countries.